Previous Use of Anti-Vascular Endothelial Growth Factor Receptor Agents Decreases Efficacy of Fruquintinib in Metastatic Colorectal Cancer Refractory to Standard Therapies - Wang, Lei; Cao, Huijiao; Jiang, Chang; He, Wenzhuo; You, Yafei; Peng, Kunwei; Jin, Yanan; Xia, Liangping (Frontiers in Oncology, 2020)
Purpose: Fruquintinib is an anti-vascular endothelial growth factor receptor (VEGFR) agent. The FRESCO trial demonstrated that patients with metastatic colorectal cancer (mCRC) refractory to standard therapies could benefit from fruquintinib with tolerable adverse events (AEs). However, the efficacy and safety of fruquintinib in clinical practice has scarcely been reported, especially in patients with previous use of anti-VEGFR agents. Methods: This retrospective study investigated the efficacy and safety of fruquintinib in patients with mCRC between January 2019 and December 2019. Progression-free survival (PFS) and overall survival (OS) were assessed by a Kaplan-Meier analysis and log-rank test. A Cox regression model was performed to identify independent prognostic factors. Results: A total of 46 patients were included. The median PFS and OS were 3.1 months (95% confidence interval [CI], 1.9–4.3 months) and 9.0 months (95% CI, 7.2–10.8 months), respectively. Patients previously treated with anti-VEGFR agents had shorter median PFS compared with those without previous use of anti-VEGFR agents (1.9 vs. 3.7 months, P = 0.006), while the median OS was similar between the two groups (8.5 vs. 9.0 months, P = 0.992). Multivariate analysis revealed that the neutrophil-lymphocyte ratio (NLR) was an independent prognostic factor in PFS (hazard ratio [HR], 2.230; 95% CI, 1.191–4.517, P = 0.014) and OS (HR, 4.221; 95% CI, 1.683-10.586; P = 0.002). The most common non-hematological and hematological AEs were hand-foot syndrome (37.0%) and anemia (39.1%), respectively. Conclusion: Fruquintinib was an effective third-line therapy in mCRC with tolerable AEs. Efficacy of fruquintinib was decreased in patients with previous use of anti-VEGFR agents. NLR was an independent prognostic factor in PFS and OS in patients treated with fruquintinib.